Covid-19 Pandemic: A Qualitative Study on Adolescents’ Stress, Anxiety, and Family Communication - Zeynep Çetin (Pakistan Journal of Medical & Health Sciences, 2022)
Eight high-school students participated in this qualitative study to investigate the adolescents’ stress, anxiety, and family communication during the COVID-19 pandemic. To collect data, a list of questions was prepared by the researchers based on experts’ opinions, and open-ended interviews were carried out with the participants. Consequently, four models were created and thoroughly investigated. According to the results, the COVID-19 pandemic led to higher levels of stress and anxiety and both positive and negative effects in the adolescents’ communication with their families. It seems that the period of social isolation adversely affected the adolescents’ interaction with their peers.